Produktivitas Feminimisasi Larva Ikan Betok (Anabas testudineus) Menggunakan Ekstrak Buah-buahan dengan Metode Dipping - Helmizuryani Helmizuryani; Boby Muslimin; Khusnul Khotimah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Helmizuryani et al, 2016.Â Productivy of Feminization of Anabas testudineus Larvae Used Fruits Extract by Dipping Method. JLSO 5(1):35-42.Anabas testudineusis one of indigenous fish in Indonesia spread on swamp and river, need attention because the population endangered and higher people consumption. This research aims to identification fruits extract function toward larvae feminization. It has dipping together with larvae for 10 hours, which doze 3 ml/l by different fruits extract.The larvae was 7 days old. After dipping, it has rearing on aquarium during 90 days became seed stage which observation sex ratio and seed growth.Â  This research was conduct on hatchery at Community Unit â€œMuliaâ€ Plaju, Palembang and Chemical Laboratory, University of Muhammadiyah Palembang from Februari until April 2016. Larvae was got from broodstock reproduction at hatchery. Experiment method used completely ramdomized design and three treatment of different fruits extract, and three repetation.The treatment are P1: the avocado extract, P2: the bengkoang extract, and P3: date palm extract. The experiment showed the higher survival rate was P2 (64,44%), the higher length growth was P1 (3,11 mm), the highest weigth growth was P1 (1,03 gr). The best sex ratio for female was P1 (74.07%).The best sex ratio for male was P2 (48,12%).